Synthesis and microstructure analysis of aligned carbon nanotube/pyrocarbon composites. (February 2015) - Patel, Harshad; Manocha, L.M.; Manocha, S.
Abstract : A two-step preparation of aligned CNT (ACNT)/pyrolytic carbon composites was carried out with chemical vapor deposition and chemical vapor infiltration by filling the space within the ACNT film with pyrolytic carbon, using methane as carbon precursor. The structure of the composites was investigated by scanning electron microscopy and Raman spectroscopy. Results showed that the CNTs were coated unevenly with densely-packed carbon spheres at 950 °C. At 1050 °C, the CNTs were uniformly coated which increased their diameters from 20–60 nm to 400–500 nm and closed pores were formed as a result of the fast formation and a slow diffusion of carbonaceous nuclei during the latter stages of deposition. At both temperatures, the density of the film increased more than four fold when the pyrolytic carbon was graphitized. [New Carbon Materials 2014, 29(5): 374–379]